Biology, Ecology and Management of Tephritid Fruit Flies in China: A Review - Yuxin He; Yijuan Xu; Xiao Chen (Insects)
Tephritid fruit flies are notoriously known for causing immense economic losses due to their infestation of many types of commercial fruits and vegetables in China. These flies are expanding, causing serious damage, and we summarized references from the last three decades regarding biological parameters, ecological performance and integrated pest management. There are 10 species of tephritid fruit flies mentioned at a relatively high frequency in China, and a detailed description and discussion in this comprehensive review were provided through contrast and condensation, including economics, distribution, identification, hosts, damage, life history, oviposition preference, interspecific competition and integrated management, in anticipation of providing effective strategies or bases for the subsequent development of new research areas and improvement of integrated management systems.